VOCES AUTORIZADAS EN TWITTER DURANTE LA PANDEMIA DE COVID-19: ACTORES, LÉXICO Y SENTIMIENTOS COMO MARCO INTERPRETATIVO PARA USUARIOS ORDINARIOS. - Sued Palmeiro, Gabriela Elisa; Cebral Loureda, Manuel (Revista de Comunicación y Salud, 2020)
This work addresses the communicative role of authorized voices on Twitter during the COVID-19 pandemic and their interaction with ordinary users. They are defined as public profile users who have a big number of followers, and whose messages are massively disseminated on the platform by ordinary users. A set of tweets was collected over two months through the Twitter API, and then a subset of data was formed with the tweets replicated more than 100 times. Labeling, data mining, and sentiment analysis techniques were applied to it. It is observed that the interpretive framework of the pandemic is modeled by the media, although there are perceptions of ordinary users about the pandemic as a time of economic, health, political and personal crisis that are not present in the authorized voices. It is concluded that the media and front-line government officials are the ones that achieved the greatest adherence and amplification of the word by ordinary users, although there is a significant gender gap between the voices of men and those of women.